A pilot study exploring the utility of a 'therapeutic research group' intervention for people experiencing psychosis related difficulties. (3rd May 2020) - Abram, M.; Awenat, Y.; Byrne, R.; Fin, M.; Finlayson, S.; Foat-Smith, G.; Galarza, M.; Haddock, G.; Jackson, P.; Lee, G.; Melia, S.; McCulla, J.; et al.
ABSTRACT: Objectives: This pilot study explored the feasibility and acceptability of using research as the basis of a therapeutic group intervention for hearing voices/auditory hallucinations. Methods: Using a Participatory Action Research methodology, seven male current or previous residents of a low secure hospital participated in the study. Participants independently conducted research on ideas that were generated and operationalised by the group, on a weekly basis over a seven-month period. Participants focused on developing a new 'easy to complete' recovery/resilience measure. The group also themselves developed a qualitative interview schedule, and participated in interviews at the conclusion of the intervention period. In addition to the four participants who engaged throughout the intervention period and contributed towards the analysis of transcripts, three other participant's (two who disengaged on moving to a new area and one who consented to participate but never attended) took part in post-intervention interviews. Results: The study demonstrated preliminary evidence supporting the utility of a 'Therapeutic Research Group' intervention for people who experience distressing voices. In addition to feedback about the positive impact participating in the group had on well-being, participants offered advice on overcoming barriers and increasing the popularity of therapeutic interventions. Participants also developed a new recovery/resilience measure (the M-PART) whose preliminary face validity appears positive. Discussion: Mental health service users/survivors can independently make important contributions to advancing knowledge and improving services. Further research examining whether 'the conducting of research' could form the basis of a therapeutic intervention is warranted. Empirical testing of the M-PART measure is also necessary.